Empowerment and Development of Kajhu Village as a Disaster Resilient Village Based on Fasterization and Ecotourism - Hasnan Hanif; Adelia Maulida; Maulana Kamal; Rina Suryani Oktari (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Kajhu Village is a coastal area within the Baitussalam District of Aceh Besar. In 2004, the village suffered significant damage due to an earthquake and ensuing tsunami, resulting in loss of life and damage to infrastructure. Despite the inherent disaster risk, Kajhu Village possesses great potential, including the scenic beauty of its coastline and the abundance of mangrove ecosystems. These natural resources can be harnessed to develop environmental and disaster-based tourism opportunities. In recognition of this potential, the Fasilitator Tangguh Bencana (FASTANA) - Tsunami and Disaster Mitigation Research Center at Universitas Syiah Kuala (TDMRC USK), an organization dedicated to community service and disaster mitigation, launched a disaster risk reduction program aimed at empowering the community and reducing the risk of disaster in Kajhu Village. Data collection involved observation and interviews with local residents. Community service activities focused on education and empowerment, including disaster preparedness education for the community and schools, promotion of the importance of protecting coastal ecosystems, and training and empowering the creative economy. Additionally, disaster literacy corners were established in schools within Kajhu Village. Through these programs, the goal was to create a community that is resilient to disaster and economically self-sufficient. By providing support and empowerment to the community, it is hoped that a new mindset can be fostered, resulting in greater independence and resilience. The disaster education provided aims to help individuals and families understand and implement effective disaster prevention strategies. The implications of the community service program in Kajhu Village are increasing community resilience and preparedness in dealing with natural disasters and developing the potential of coastal ecosystems to become sustainable ecotourism attractions, providing inspiration for communities in other areas to adopt a participatory and structured approach in an effort to increase resilience and disaster preparedness and developing the potential of coastal ecosystems.